2013
DOI: 10.1371/journal.pone.0065088
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Effects on Memory Reconsolidation Favor a Learning Model of Delusions

Abstract: Delusions are the persistent and often bizarre beliefs that characterise psychosis. Previous studies have suggested that their emergence may be explained by disturbances in prediction error-dependent learning. Here we set up complementary studies in order to examine whether such a disturbance also modulates memory reconsolidation and hence explains their remarkable persistence. First, we quantified individual brain responses to prediction error in a causal learning task in 18 human subjects (8 female). Next, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 103 publications
(147 reference statements)
4
39
0
Order By: Relevance
“…In general, however, the sustainability effect of ketamine remains poorly understood. A recent study reported enhanced memory reconsolidation 24 h after ketamine infusion [91]. Enhanced memory consolidation and reconsolidation were also found 24 h after memantine-an NMDA receptor antagonist-administration in day-old chicks [92].…”
Section: Behavior Effects Of Ketamine Infusionmentioning
confidence: 92%
“…In general, however, the sustainability effect of ketamine remains poorly understood. A recent study reported enhanced memory reconsolidation 24 h after ketamine infusion [91]. Enhanced memory consolidation and reconsolidation were also found 24 h after memantine-an NMDA receptor antagonist-administration in day-old chicks [92].…”
Section: Behavior Effects Of Ketamine Infusionmentioning
confidence: 92%
“…24 By creating new associations, reactivating them under ketamine, and then testing their strength, we observed that ketamine-reactivated associations were strengthened. 87 In humans, this effect correlated with ketamine-induced psychosis and PE brain signal. 87 …”
Section: Delusion Persistencementioning
confidence: 95%
“…Likewise, when delusions are questioned, bringing them to mind may actually serve to reinforce rather than to disrupt the memory. 8,27,87 The idea here is that re-evocation of an association may strengthen a memory even when it is not formally reinforced. 27 We have modeled this process in humans and rats with ketamine.…”
Section: Delusion Persistencementioning
confidence: 99%
“…Unfortunately, although ketamine has many suitable characteristics, such as maintained cardiorespiratory stability, bronchodilation, and potent analgesia, it can cause problematic psychiatric phenomena. In subsedative doses in adults it has been shown to cause several of the negative symptoms of schizophrenia [3,4].…”
Section: Choice Of Agentsmentioning
confidence: 99%